Pretext for Religious Violence in Indonesia: An Anthropolinguistic Analysis of Fatwas on Ahmadiyya - Fariz Alnizar (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2019)
This study uses an anthropolinguistic approach to examine two Majelis Ulama Indonesia (MUI) fatwa texts regarding Ahmadiyya. First, it shows that there are significant differences between the 1980 and 2005 fatwas. Second, in terms of their lexicon, the 1980 fatwa uses the phrase